PENGGUNAAN MENDELEY DALAM MENINGKATKAN KUALITAS PENULISAN SKRIPSI MAHASISWA PROGRAM STUDI ADMINISTRASI PUBLIK UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA - Fetni; Puji Prio Utomo; Mardiana (Journal Publicuho, 2023)
This study discusses how Mendeley is used to improve the quality of student thesis writing. The goal is to understand the quality of student thesis writing using Mendeley. This paper is a qualitative descriptive with the aim of analyzing the data compiled with primary and/or secondary data and then linking the data to relevant theories. Research informants come from findings or surveys conducted on public administration students by means of purposive sampling—data processing methods with participatory observation, in-depth interviews, and documentation. Data analysis uses descriptive qualitative that is able to produce quality data. The results of this study show that the use of Mendeley provides solutions related to student final assignment writing so that students become more efficient and faster in completing their final assignment or thesis. Students no longer need to make citationsbibliographiesaphy manually because Mendeley can automatically create a bibliography. While previously students had difficulty finding references for their final project, they automatically have no more difficulties with Mendeley because this application can be opened directly to Google so that whatever students need they can search immediately.